STRATEGI KOMUNIKASI HUMAS POLRESTA SURAKARTA DALAM SOSIALISASI APLIKASI SIOLOS - Yudha, Yudha Prasetyo; Wisudawanto, Rahmat; Putri, Sofia Ningsih Rahayu (JURNAL KOMUNITAS, 2023)
SIOLOS application stands for Sistem Operasi Layanan Online. The SIOLOS application itself is an application released by the Surakarta Police which is useful for improving information services to the public, especially online services. The function of this application includes various uses, namely there are many features such as procedures for making a SIM, SKCK, and so on.The public relations of Polresta Surakarta used social media Instagram with the account name @polrestasurakarta. The study aimed to explain the public relations strategy of Polresta Surakarta in disseminating the SIOLOS application. This research used a descriptive qualitative research method. Methods of collecting data used interviews and documentation. The results showed that the Polresta Surakarta Public Relations strategy in socializing the SIOLOS application, namely publication, event, news, corporate identity, community involvement, lobbying and negotiation, and corporate social responsibility. The public relations of Polresta Surakarta were quite effective in conducting its socialization because it used Instagram social media, which has about 65 thousand followers and is widely accessed by the public.